The Role of Transforming Growth Factor β1 in the Regulation of Blood Pressure - Matsuki, Kota (Curr Hypertens Rev, 2014)
Although human association studies suggest a link between polymorphisms in the gene encoding transforming growth factor (TGF) β1 and differing blood pressure levels, a causative mechanism for this correlation remains elusive. Recently we have generated a series of mice with graded expression of TGFβ1, ranging from approximately 10% to 300% compared to normal. We have found that blood pressure and plasma volume are negatively regulated by TGFβ1. Of note, the 10% hypomorph exhibits primary aldosteronism and markedly impaired urinary excretion of water and electrolytes. We here review previous literature highlighting the importance of TGFβ signaling as a natriuretic system, which we postulate is a causative mechanism explaining how polymorphisms in TGFβ1 could influence blood pressure levels.